Long-term efficacy of anti-PD1 therapy in Hodgkin lymphoma with and without allogenic stem cell transplantation. (July 2019) - Manson, Guillaume; Mear, Jean-Baptiste; Herbaux, Charles; Schiano, Jean-Marc; Casasnovas, Olivier; Stamatoullas, Aspasia; Deau, Bénédicte; Schmitt, Anna; Garnier, Georges; Regny, Caroline; Bouabdallah, Krimo; Moles-Moreau, Marie-Pierre; et al.
Abstract: Introduction: Long-term efficacy of anti-PD1 therapy and the need for a consolidation with allogenic haematopoietic stem cell transplantation (allo-HSCT) remain unclear in patients with relapsed/refractory (R/R) Hodgkin lymphoma (HL). Methods: We retrospectively analysed 78 patients with R/R HL treated with nivolumab in the French Early Access Program and compared their outcomes according to subsequent allo-HSCT. Results: After a median follow-up of 34.3 months, the best overall response rate was 65.8%, including 38.2% complete responses (CRs). The median progression-free survival (PFS) was 12.1 months. Patients reaching a CR upon nivolumab had a significantly longer PFS than those reaching a partial response (PR) (median = not reached vs 9.3 months, p < 0.001). In our cohort, 13 patients who responded ( i.e . in CR or PR) to nivolumab monotherapy underwent consolidation with allo-HSCT. Among responding patients, none of those who underwent subsequent allo-HSCT (N = 13) relapsed, whereas 62.2% of those who were not consolidated with allo-HSCT (N = 37) relapsed (p < 0.001). There was no difference in overall survival (OS) between the two groups. Five of 6 patients who were not in CR at the time of transplantation (4 PRs and 1 progressive disease) converted into a CR after allo-HSCT. Conclusion: Most patients with R/R HL treated with anti-PD1 monotherapy eventually progressed, notably those who did not achieve a CR. Patients undergoing consolidation with allo-HSCT after anti-PD1 therapy experienced prolonged disease-free survival compared with non-transplanted patients, but this difference did not translate into a benefit in OS. This information should be considered when evaluating the risk/benefit ratio of allo-HSCT after anti-PD1 therapy. Highlights: Most patients with relapsed/refractory Hodgkin lymphoma eventually progressed during anti-programmed cell death-1 (anti-PD1) therapy. In responding patients, the relapse rate was lower in patients consolidated with allogenic haematopoietic stem cell transplantation (allo-HSCT). Among responders, subsequent allo-HSCT was not associated with a greater overall survival.